2011
DOI: 10.1108/02637471111139446
|View full text |Cite
|
Sign up to set email alerts
|

Incursion of non‐professionals into property management practice in Nigeria

Abstract: PurposeThe paper seeks to identify the factors that are responsible for the incursion of non‐professionals, otherwise called quacks, into property management practice in Nigeria.Design/methodology/approachPrimary data were collected with the aid of questionnaires served on 270 estate surveying firms based in the study area. The proportion method was used to determine the factors that are significantly responsible for the daily incursion of non‐professionals whose activities have negatively affected real estate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…However, coming at a close third position in the ranking of the effects of non-professionals' involvement on real estate agency practice is unhealthy competition with a mean score of 4.16. The inherently lucrative nature of real estate agency given the characteristic high transaction values associated with real estate has invited competition from many categories of individuals; the unemployed, artisans, landlords and all manners of people thereby resulting into unhealthy rivalry with non-professionals (Oladokun and Ojo, 2011). This has given rise to flagrant contempt for professionalism in forms of gazumping, unduly long chain of agents, fraudulent increases in sale prices, etc, while real estate service consumers are often not able to distinguish between the professionals and those allegedly laying claim to real estate professionalism.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, coming at a close third position in the ranking of the effects of non-professionals' involvement on real estate agency practice is unhealthy competition with a mean score of 4.16. The inherently lucrative nature of real estate agency given the characteristic high transaction values associated with real estate has invited competition from many categories of individuals; the unemployed, artisans, landlords and all manners of people thereby resulting into unhealthy rivalry with non-professionals (Oladokun and Ojo, 2011). This has given rise to flagrant contempt for professionalism in forms of gazumping, unduly long chain of agents, fraudulent increases in sale prices, etc, while real estate service consumers are often not able to distinguish between the professionals and those allegedly laying claim to real estate professionalism.…”
Section: Resultsmentioning
confidence: 99%
“…This echoes Latessa et al 's (2002) earlier work which found that non-professionals are usually more accessible, take more time to attend to clients and seem to understand clients better. Oladokun and Ojo (2011) further notes that most uninformed real estate service consumers believe that trained professionals charge more fees than the non-professionals (Oladokun and Ojo, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nemieboka (2010) argued that the activities of quacks in the real estate sector are responsible for the high sales and rental values of real estate. A study by Oladokun and Ojo (2011) looked into the incursion of nonprofessionals in property management practice in Nigeria, while Oloyede et al (2011) discussed the issues confronting the estate surveying and valuation profession in Nigeria and gave four reasons why trespassers continue to flow into real estate business. The first reason was given as the inadequacy of registered estate surveyors and valuers to satisfy the local demand for their services.…”
Section: An Overview Of Quackery In Built Environment Professions In Nigeriamentioning
confidence: 99%
“…They contribute to overall project performance by deploying appropriate competencies (Nkado and Meyer, 2001;Dada and Jagboro, 2012). These competencies are aimed at accomplishing projects that meet clients' value expectations (Olanrewaju and Anahve, 2015). However, quackery has caused many damages to the practice of the profession, with attendant consequences on the patronage of quantity surveying services and construction project delivery at large.…”
Section: Introductionmentioning
confidence: 99%